JENIS DAN MAKNA KONJUNGSI PADA TERJEMAHAN ALQURAN SURAH AL-MA’IDAH - Maulani, Intan Suri; Ermanto, Ermanto; Juita, Novia (Universitas Negeri Padang, 2017)
This study aims to describe: (1) types of conjunction contained alquran surah Al-Ma’idah, (2) expose conjunction meaning contained in the translation of alquran surah Al-Ma’idah. This types of research is qualitative by using descriptive method. The data of this research is a sentence in the translation of alquran surah Al-Ma’idah containing are surah Al-Ma’idah and Al-Ma’idah alquran translation.Based on the research data, two types of conjunctions an ten conjunctions are found. These types of conjunctions are coordinated conjunctions and subordinate conjunctions. Coordinate conjunctuons are found that is: and, or, and but. The subordinate conjunction found is: when, after, before, until, during, when, if, because, that, with, in order, though. The meaning of conjunction is found: meaning the addition, choice, resistance, temporal/time, cause, condition, not condition, expectation, objek, and manner. Keywords: conjunction, Alquran, translation of surah Al-Ma’idah